Epidemiological study of gonorrhea - Sopungco, Herminda O. A.
An epidemiological study on the commonly called "the clap", "gleet" or the "drip", a gonorrhea caused by the gonococus. As a common venereal diseases, its control was cited as one of the major problems in medical practice, since it occurs 10 or more times as frequently as syphilis.